Exotic species of freshwater decapod crustaceans in the state of São Paulo, Brazil: records and possible causes of their introduction - Magalhaes, C.; Bueno, SLS; Bond-Buckup, G.; Valenti, Wagner Cotroni [UNESP]; Da Silva, HLM; Kiyohara, F.; Mossolin, E. C.; Rocha, S. S. (Springer, 2005)
Based on recent surveys of the freshwater decapod fauna, distributional data of five exotic species of freshwater decapod crustaceans for the hydrographic basins of the state of São Paulo are presented, as part of a large initiative for a comprehensive survey of the state's biodiversity (BIOTA-FAPESP Program). These species are the North American crayfish Procambarus clarkii (Girard) (Cambaridae), the crab Dilocarcinus pagei Stimpson (Trichodactylidae) from the Amazon and Paraguay/lower Parana River Basins, and the palaemonid shrimps Macrobrachium rosenbergii (De Man), from the Indo-Pacific region, Macrobrachium amazonicum (Heller) and Macrobrachium jelskii (Miers), both from the Orinoco, Amazon and the Paraguay/lower Parana River Basins. Possible modes by which their introduction might have occurred are commented upon and potential consequences are discussed.
Keywords: anthropogenic dispersal; biological invasion; Brazil; crustacea; Decapoda; exotic species; freshwater; São Paulo